Modelling the Optimal Electricity Mix for Togo by 2050 Using OSeMOSYS - Esso-Wazam Honoré Tchandao; Akim Adekunlé Salami; Koffi Mawugno Kodjo; Amy Nabiliou; Seydou Ouedraogo (International Journal of Renewable Energy Development, 2023)
This work uses bottom-up modeling to explore the future evolution trajectories of the electricity mix in Togo by 2050. The objective is to investigate the evolution of the mix and the future investments needed to achieve the sustainable energy and climate change goals. Three scenarios were developed using OSeMOSYS. The reference scenario, named Business As Usual, closely reflects the evolution of the Togolese electricity sector under a business-as-usual assumption and planned capacity increases up to 2030. The second scenario, Net Zero by 2050, is based on the first scenario while ensuring that CO2 emissions cancel out in 2050 by following the Weibull law. The third scenario called Emission Penalty aims not only at the integration of renewable energies like the second one but also at the least cost electricity mix if emission penalties are applied. The results of the cost optimization indicate that photovoltaic and importation are the optimal choices ahead of gas and hydropower. The renewable energy aspect of the electricity mix is more highlighted in the last scenario. At the same time, the model shows that greater energy independence is achievable at the cost of a transitory increase in the cost of the electricity system. A tenfold investment effort is needed in 2030 to ensure either continuity of the status quo or a shift in strategy.